Perceived Loss of Social Contact and Trauma Symptoms among Adolescents Who Have Experienced Sexual Abuse. Issue 3 (3rd April 2019) - Bi, Shuang; Rancher, Caitlin; Johnson, Emily; Cook, Katrina; McDonald, Renee; Jouriles, Ernest N.
ABSTRACT: Child sexual abuse (CSA) is a robust predictor of trauma symptoms. Past research has identified many correlates of trauma symptoms following disclosure of CSA. Theory suggests that loss of social contact may be another important contributor to adolescents' trauma symptoms following CSA. A clinical sample of 166 adolescents (95% female) between 11 and 19 years ( M = 13.80, SD  = 1.87) reported on perceived loss of social contact, the extent to which the CSA was coercive, appraisals of self-blame for the abuse, supportiveness of a primary non-abusing caregiver, and trauma symptoms. The adolescent's relationship to the abuser, abuse severity and duration were coded from forensic interviews. Results indicated that greater perceived loss of social contact was associated with higher levels of trauma symptoms, even after controlling for other correlates of trauma symptoms and demographic variables. These findings suggest that perceived loss of social contact may be an important variable to consider in assessing and intervening with adolescents who have been sexually abused.